PENGARUH SOCIAL MEDIA MARKETING DAN ADVERTISING TERHADAP BRAND AWARENESS SUBURBIA COFFEE - Yudistira, Ahmad Sidiq (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to identify the effects of communication mix, social media marketing, and advertising on the brand awareness of Suburbia Coffee’s target customers. This research is categorized as explanatory research, a study conducted through presenting the positions of variables being studied and the relationship between them. The number of samples used in this study were 100 respondents. The data was harvested through questionnaires and was processed in SPSS version 26. This research finds that social media marketing and advertising simultaneously have positive and significant effect on the brand awareness of Suburbia Coffee’s prospective customers. Further, partial wise, social media marketing produces a significant effect on the awareness toward Suburbia Coffee, while the effect of advertising is significant and dominant.